"La argentinidad al palo": O "registro" a "vigilância" e o "controle" efetuados pelos agentes da DIPBA sobre as intituiçoes judaicas de La Plata - Kahan, Emmanuel Nicolás (2009)
The opening of the archives of Brazil's political police forces - the DEOPS-SP and the DOPS-RJ, by their Portuguese denominations - has allowed the de-velopment of a research field that includes a variety of analytical perspectives. On the contrary, judging by the amount of research projects on its documen-tary sources, the opening to public scrutiny of the Dirección de Inteligen-cia de la Policía de la provincia de Buenos Aires (DIPBA), which took place in 2003, has not attracted the attention of social scientists and researchers. This paper seeks to give an account of the specificities of the DIPBA's archive through a revision of its documentary collection, focusing in the forms and the representations on the base of which the police intelligence agents carried out the tasks of "registering", "vigilance" and "control" on the institutions of the Jewish community in the city of La Plata.